2016
DOI: 10.1371/journal.pone.0161120
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Toxin Complex Gene Clusters and Insect Toxicity of Bacteria Representing Four Subgroups of Pseudomonas fluorescens

Abstract: Ten strains representing four lineages of the Pseudomonas fluorescens group (P. chlororaphis, P. corrugata, P. koreensis, and P. fluorescens subgroups) were evaluated for toxicity to the tobacco hornworm Manduca sexta and the common fruit fly Drosophila melanogaster. The three strains within the P. chlororaphis subgroup exhibited both oral and injectable toxicity to the lepidopteran M. sexta. All three strains have the gene cluster encoding the FitD insect toxin and a ΔfitD mutant of P. protegens strain Pf-5 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 62 publications
(103 reference statements)
5
49
0
Order By: Relevance
“…In pathogens, the Gac sensor kinase system controls virulence gene expression (Heeb and Haas, 2001). It is also found that the Gac/Rsm system of PcO6 is required for the expression of the insecticidal activity to the tobacco hornworm (Rangel et al, 2016), and to the root knot nematode (Lee et al, 2011(Lee et al, , 2017. In addition, the Gac system is shown to be important in expression of gene expression in the inhibition of fungal growth by PcO6 Oh et al, 2013a;Park et al, 2011).…”
Section: Gac/rsm System a Master Switch For Global Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathogens, the Gac sensor kinase system controls virulence gene expression (Heeb and Haas, 2001). It is also found that the Gac/Rsm system of PcO6 is required for the expression of the insecticidal activity to the tobacco hornworm (Rangel et al, 2016), and to the root knot nematode (Lee et al, 2011(Lee et al, , 2017. In addition, the Gac system is shown to be important in expression of gene expression in the inhibition of fungal growth by PcO6 Oh et al, 2013a;Park et al, 2011).…”
Section: Gac/rsm System a Master Switch For Global Regulationmentioning
confidence: 99%
“…Hosts other than plants also are affected by colonization with PcO6, because this bacterium possessed insecticidal capacity. This bacterium showed insecticidal activity on the tobacco hornworm (Rangel et al, 2016) and on nematodes (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…TcAs are not only present in insects and human pathogenic bacteria, but they have been also identified in plant pathogenic bacteria such as Pseudomonas syringae and Pseudomonas fluorescens 31 . Although we have not studied TcA from these bacteria, based on our study, we propose that all TcAs, including those of plant pathogenic bacteria share the same architecture and mechanism of action.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, based on the phylogenetic analysis, P. cedrina was clustered into fluorescens subgroup and certain strains of fluorescens subgroup exhibited insecticidal activity. In addition, two types of insect toxin genes: fluorescens insecticidal toxin (FitD) and Toxin complex (Tc) proteins have been identified (Rangel et al, ; Ruffner et al, ). However, in this study, supernatant of P. cedrina lost larvicidal activity, while supernatant of B. thuringiensis exhibited high larvicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The neighbor‐joining phylogenetic tree was constructed by MEGA5.1 with the closest sequences from NCBI and related 16S rRNA of Pseudomonas spp. from Rangel et al ().…”
Section: Methodsmentioning
confidence: 99%